2002
DOI: 10.1176/appi.ps.53.9.1103
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of ADHD Among Children in Pediatric and Psychiatric Clinics

Abstract: Children with ADHD from both psychiatric and pediatric practices have prototypical symptoms of the disorder; high levels of comorbidity with mood, anxiety, and disruptive behavior disorders; and impairments in cognitive, interpersonal, and academic function that do not differ by ascertainment source. These findings suggest that children cared for in pediatric practice have similar levels of comorbidity and dysfunction as psychiatrically referred youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 51 publications
10
71
0
3
Order By: Relevance
“…To a lesser degree, children in the non-psychiatric sample also had multiple types of comorbidities and similar social problems. These results are consistent with Busch et al [29], whose findings contradicted previous studies that showed non-psychiatric samples as less compromised than psychiatric samples [1,[26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…To a lesser degree, children in the non-psychiatric sample also had multiple types of comorbidities and similar social problems. These results are consistent with Busch et al [29], whose findings contradicted previous studies that showed non-psychiatric samples as less compromised than psychiatric samples [1,[26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…A amostra re d u z i d a deste estudo pode ter limitado estas conclusões já que apenas 4 casos de crianças com o tipo hiperativo foram encontradas. Tr a n s t o rnos psiquiátricos comórbidos são comuns no TDAH 1 9 , part i c u l a rmente transtornos disruptivos, de humor e de ansiedade 9,13,[21][22][23] . Nesta amostra, a maioria das crianças com TDAH (57,14%) manifestava alguma das comorbidades estudadas, em concordância com outros estudos 1 3 , 1 6 , 2 3 .…”
Section: Média De Idade (Anos) ±unclassified
“…(Biederman et al, 2006;Biederman et al, 2010b) (Busch et al, 2002) Subjects were derived from two identically designed longitudinal case-control family studies of ADHD. These studies recruited male and female probands aged 6 to 17 years with DSM-III-R ADHD (N=140 boys, N=140 girls) and without ADHD (i.e.…”
Section: Methodsmentioning
confidence: 99%